Occurrence and spatial distribution of paralytic shellfish toxins in seawater and marine organisms in the coastal waters of Qinhuangdao, China. (February 2023) - Cao, Yadong; Qiu, Jiangbing; Li, Aifeng; Zhang, Lei; Yan, Guowang; Ji, Ying; Zhang, Jingrui; Zhao, Peng; Wu, Xizhen
Abstract: In recent years, paralytic shellfish toxins (PSTs) have been prevalent in the coastal waters of Qinhuangdao, the west coast of the Bohai Sea, China. The content of PSTs in shellfish often exceeded the regulatory limit of 800 μg STX equivalent (eq.) kg −1, which poses a serious threat to human health. In this study, two surveys were conducted in May 2021 and May 2022 to investigate the distribution of PSTs in the coastal waters of Qinhuangdao. Seawater, surface sediment, phytoplankton, zooplankton, and other marine organism samples were collected, and the composition and concentration of PSTs were analyzed by liquid chromatography with tandem mass spectrometry (LC-MS/MS). Results showed that multiple PST components were detected in all seawater samples collected at different depths, mainly including GTX1/4, GTX2/3, dcGTX2, STX and C1/2, and the highest concentration of PSTs reached 244 ng STX eq. L −1 . The sediment samples also contained low levels of C1/2 and GTX2/3. Trace amounts of C1/2 and GTX1-4 were detected in phytoplankton and zooplankton. Moreover, all bivalve shellfish samples were found to contain PSTs, and the scallop Azumapecten farreri and the ark clam Anadara kagoshimensis showed relatively high concentrations of 607 and 497 μg STX eq. kg −1, respectively. In addition, low levels of PSTs were also found in some non-traditional PST vectors, including whelk Rapana venosa, octopus Amphioctopus ovulum, goby Ctenotrypauchen chinensis, and greenling Hexagrammos agrammus . Results of this study improve the understanding of the distribution of PSTs in seawater and marine organisms and the potential risk of persistent PSTs in seawater to marine ecosystems and human health. Graphical abstract: Image 1 Highlights: Concentrations of PSTs reached up to 244 μg STX equivalent L −1 in seawater. Sediment samples contained low levels of C1/2 and GTX2/3. Phytoplankton and zooplankton contained small amounts of C1/2 and GTX1-4. PSTs were prevalent in bivalve mollusks. Low levels of PSTs were found in gastropod, cephalopod and fish samples.